2022
DOI: 10.1186/s12872-022-02861-w
|View full text |Cite
|
Sign up to set email alerts
|

Elevated NT-proBNP levels are associated with CTP ischemic volume and 90-day functional outcomes in acute ischemic stroke: a retrospective cohort study

Abstract: Objective To investigate the impact of N-terminal pro-B-type natriuretic peptide (NT-proBNP) on CTP infarct core volume and poor 90-day functional outcomes in acute ischemic stroke (AIS). Methods A total of 403 hospitalized patients with AIS in the Stroke Center of the First Hospital Affiliated to Soochow University were enrolled from March 2018 to January 2021. The association between NT-proBNP and clinical outcomes in acute ischemic patients was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The BNP levels were shown to negatively correlate with a favorable outcome within 24 h of stroke onset [ 41 ]. Recent studies suggested that BNP and NT-proBNP may have use in predicting stroke risk in patients with heart failure with preserved ejection fraction [ 42 ], prognostic potential for functional outcome after AIS [ 43 , 44 ], and use in optimizing the management of stroke associated to heart disease [ 45 ]. Further work correlating BNP and NT-proBNP expression in AIS clots with longer-term patient outcome measures of stroke severity could yield further interesting insights.…”
Section: Discussionmentioning
confidence: 99%
“…The BNP levels were shown to negatively correlate with a favorable outcome within 24 h of stroke onset [ 41 ]. Recent studies suggested that BNP and NT-proBNP may have use in predicting stroke risk in patients with heart failure with preserved ejection fraction [ 42 ], prognostic potential for functional outcome after AIS [ 43 , 44 ], and use in optimizing the management of stroke associated to heart disease [ 45 ]. Further work correlating BNP and NT-proBNP expression in AIS clots with longer-term patient outcome measures of stroke severity could yield further interesting insights.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a metaanalysis concluded that PTFV1 is an independent predictor of IS 9) ; however, a subsequent prospective study questioned its reliability 10) . Similarly, while NT-pro BNP has been identified as useful for predicting the functional outcomes and mortality in AIS patients 11,12) , other studies have found that elevated levels of NT-pro BNP do not necessarily correlate with the 3-month mortality in AIS patients who do not show any obvious myocardial damage 13) . Additionally, some evidence suggests that composite indicators of the myocardial function may offer a more nuanced prognostic value than single markers 14) .…”
Section: Discussionmentioning
confidence: 99%
“…While previous large-scale studies have indicated the significance of ACM markers in gauging the risk of adverse cardiac events, such as atrial fibrillation (AF) 22,23) , myocardial infarction (MI) 24,25) , and HF 26) , their role in st roke prognosis remains underexplored. Several small-sample retrospective studies have found that some ACM-related markers are associated with death and disability after IS 11,12) . However, some results remain controversial in different research contexts 13) .…”
Section: Survival Analysis Of Acm In Patients With Noncardioembolic S...mentioning
confidence: 99%
“…Second, high NT-proBNP levels might indicate an underlying atrial fibrillation in ischemic stroke patients, who remained cryptogenic after the initial workup. 21 As (untreated) cardioembolic stroke etiology has a high rate of recurrent vascular events and often leads to severe stroke syndromes with larger infarct size, 1,27 this could in part explain the higher rate of post-stroke mortality in patients with high NT-proBNP levels at admission. These considerations are further supported by a trend toward a higher number of recurrent vascular events in patients with NT-proBNP levels above 794 pg/mL in our cohort.…”
Section: Discussionmentioning
confidence: 99%